Grenzenlose Enthüllungen? Medien zwischen Öffnung und Schließung - Rußmann, Uta; Beinsteiner, Andreas; Ortner, Heike; Hug, Theo (innsbruck university press, 2012)
The current media landscape is often attributed a tendency to disclosure and openness. Social network sites blur the boundaries between the private and the public, platforms such as WikiLeaks and OpenLeaks publish secret material, while file-sharing networks and open-content licenses make previously proprietary content publicly accessible. These developments are intertwined with, at first sight, opposing tendencies of containment, control and closure. Communication on the Internet is becoming increasingly linked to the mediation of individual private sector actors such as Google or Facebook. Online and offline, new information and communication technologies are enabling more and more comprehensive forms of surveillance while the re-use of data takes place in camera. The contributions of this volume deal with different aspects of this complex field of tension.